Advances in Airborne Lidar Systems and Data Processing - Hyyppä, Juha (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This edition is a reprint of the Special Issue published online in the open access journal Remote Sensing (ISSN 2072-4292) from 2016-2017 (available at: http://www.mdpi.com/journal/remotesensing/special issues/rsALS), complemented by selected articles published in Remote Sensing